A Novel Noninvasive Method for Measuring Fatigability of the Quadriceps Muscle in Noncooperating Healthy Subjects. (21st July 2015) - Poulsen, Jesper B.; Rose, Martin H.; Møller, Kirsten; Perner, Anders; Jensen, Bente R.
Abstract : Background . Critical illness is associated with muscle weakness leading to long-term functional limitations. Objectives . To assess the reliability of a novel method for evaluating fatigability of the quadriceps muscle in noncooperating healthy subjects. Methods . On two occasions, separated by seven days, nonvoluntary isometric contractions (twitch and tetanic) of the quadriceps femoris muscle evoked by transcutaneous electrical muscle stimulation were recorded in twelve healthy adults. For tetanic contractions, the Fatigue Index (ratio of peak torque values) and the slope of the regression line of peak torque values were primary outcome measures. For twitch contractions, maximum peak torque and rise time were calculated. Relative (intraclass correlation, ICC3.1 ) and absolute (standard error of measurement, SEM) reliability were assessed and minimum detectable change was calculated using a 95% confidence interval (MDC95% ). Results . The Fatigue Index (ICC3.1, 0.84; MDC95%, 0.12) and the slope of the regression line (ICC3.1, 0.99; MDC95%, 0.03) showed substantial relative and absolute reliability during the first 15 and 30 contractions, respectively. Conclusion . This method for assessing fatigability of the quadriceps muscle produces reliable results in healthy subjects and may provide valuable data on quantitative changes in muscle working capacity and treatment effects in patients who are incapable of producing voluntary muscle contractions.